Pembangunan Pariwisata Pantai Tamban Desa Tambak Rejo Kabupaten Malang dalam Perspektif Peran Serta Masyarakat dan Pemerintah Desa - Willy Tri Hardianto; Elfrida Hoar Lebo; Firman Firdausi (Universitas Sultan Ageng Tirtayasa, 2023)
This study raises the theme of the Role of the Community and the Role of the Village Government in Tamban Beach Tourism Development in Malang Regency. Since the establishment of a tourist village by the Malang Regency government, the community has begun to participate in building and maintaining existing tourism. With a low average education, of course new problems will arise. This research was conducted to determine the role of the community in the development and development of tourism, namely Tamban Beach which is located in Tambak Rejo Village. This research uses a qualitative approach. Data collection techniques used in this study were interviews, observation, and documentation. to analyze the data, namely by data correlation, data reduction, data presentation, and drawing conclusions. The results of the study show that the community's role in tourism development through tourism programs uses training and product development strategies in the tourism village. Tambak Rejo Village as the person in charge of tourism at Tambak Beach carries out a promotional strategy by making posters that will be posted on the streets around tourism in Tambak Rejo Village and then through social media, namely the Tambak Rejo village website itself. The community is also one of the supporting factors in planning tourism development in Tambak Rejo Village, but it cannot be denied that there are still several inhibiting factors from tourism development carried out by the Government and the founders of Tamban beach tourism, namely awareness from several communities regarding the development and utilization of tourist villages. what the manager did and did not rule out the fact that the last two years the tourism business was affected by the Covid 19 pandemic, although now it is slowly starting to revive